Ireland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper reviews public expenditure efficiency in Ireland. Evidence suggests that while Ireland is a low spending country, it achieves a generally efficient use of public funds, with some key differences across sectors. Although the overall space for budgetary savings appears limited, further spending efficiency could help contain cost pressures coming from the demographic challenge of an aging population and improve the quality of public services. It could also help rechannel spending toward more productive uses, for instance by increasing public investment relative to current expenditure, and support the competitive position of the Irish economy and its growth potential.